Formative research to develop theory-based messages for a Western Australian child drowning prevention television campaign: Study protocol - Denehy, Mel; Crawford, Gemma; Leavy, Justine; Nimmo, L.; Jancey, Jonine (BM J Group, 2016)
© 2016, BMJ Publishing Group. All rights reserved.Introduction: Worldwide, children under the age of 5 years are at particular risk of drowning. Responding to this need requires the development of evidence-informed drowning prevention strategies. Historically, drowning prevention strategies have included denying access, learning survival skills and providing supervision, as well as education and information which includes the use of mass media. Interventions underpinned by behavioural theory and formative evaluation tend to be more effective, yet few practical examples exist in the drowning and/or injury prevention literature. The Health Belief Model and Social Cognitive Theory will be used to explore participants' perspectives regarding proposed mass media messaging. This paper describes a qualitative protocol to undertake formative research to develop theory-based messages for a child drowning prevention campaign. Methods and analysis: The primary data source will be focus group interviews with parents and caregivers of children under 5 years of age in metropolitan and regional Western Australia. Qualitative content analysis will be used to analyse the data. Ethics and dissemination: This study will contribute to the drowning prevention literature to inform the development of future child drowning prevention mass media campaigns. Findings from the study will be disseminated to practitioners, policymakers and researchers via international conferences, peer and non-peer-reviewed journals and evidence summaries. The study was submitted and approved by the Curtin University Human Research Ethics Committee.